Mesothelial mesenteric cyst. Case report - Torres, José Enrique; Perrone Arballo, Gonzalo; Salvatierra, Martín (Cirugía del Uruguay, 2021)
Mesenteric cysts are rare abdominal tumors. Its incidence is 1/100,000 in adults. It can compromise any sector of the mesentery, being more frequent in ileon. They are usually benign, and their pathogenesis is unknown. Its preoperative diagnosis is difficult as clinical presentation is variable. They are usually asymptomatic presenting as an incidental finding. Symptoms are secondary to size or complications. Its treatment is surgical by exeresis of the injury. The definitive diagnosis is anatomopathological. We present the case of a right mesocolon cyst successfully resolved by laparoscopic approach.